2012
DOI: 10.1021/jp307668g
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast Electron Trapping at the Surface of Semiconductor Nanocrystals: Excitonic and Biexcitonic Processes

Abstract: Aging of semiconductor nanocrystals (NCs) is well-known to attenuate the spontaneous photoluminescence from the band edge excitonic state by introduction of nonradiative trap states formed at the NC surface. In order to explore charge carrier dynamics dictated by the surface of the NC, femtosecond pump/probe spectroscopic experiments are performed on freshly synthesized and aged CdTe NCs. These experiments reveal fast electron trapping for aged CdTe NCs from the single excitonic state (X). Pump fluence depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(74 citation statements)
references
References 118 publications
6
66
0
Order By: Relevance
“…The spectral distribution gives info mation on t e occu ence, population and dept s of t e su face t aps." 18 Findings from conductance spectroscopy 24 and cyclic voltammetry 25 experiments have been cited in support of this model, and the model proposed by Weller has been adopted by others. 26 In the 1990s, t eo etical wo by W aley's g oup found t at an intense surface state with high oscillator strength could occur within the band gap of a CdSe nanocluster.…”
Section: Historymentioning
confidence: 91%
See 3 more Smart Citations
“…The spectral distribution gives info mation on t e occu ence, population and dept s of t e su face t aps." 18 Findings from conductance spectroscopy 24 and cyclic voltammetry 25 experiments have been cited in support of this model, and the model proposed by Weller has been adopted by others. 26 In the 1990s, t eo etical wo by W aley's g oup found t at an intense surface state with high oscillator strength could occur within the band gap of a CdSe nanocluster.…”
Section: Historymentioning
confidence: 91%
“…Considerable recent work has suggested that the NCs within an ensemble are far from homogeneous in their decay pathways. 23,[25][26][27] Thus, we propose that the percentage of NCs within the ensemble which emit in the first place is a temperature-dependent quantity, n(T).…”
Section: Marcus-jortner Electron Transfer: a More Complete Picturementioning
confidence: 99%
See 2 more Smart Citations
“…[66,129] Engineering of surface traps to control recombination rate is critical for the design of sensitive and fast photoconductive detectors, while suppres- properties. [3,124,129,[132][133][134][135][136][137] Apart from an early report in Bi 2 S 3 nanocrystals with band gap at 1.7 eV, [138] to the best of our knowledge, no systematic investigation of the excited-state dynamics in bismuth sulfide has been reported until now. shows the presence of rod shaped particles with average sizes of 29 nm (14% polydispersity) and of 14 nm (19% polydispersity).…”
Section: Resultsmentioning
confidence: 99%